HUMAN RESOURCES MANAGEMENT IN IMPROVING TEACHER COMPETENCE THROUGH QIRA'ATI METHOD TRAINING AT AL-QUR'AN IN TK AL-QUR’AN AN-NADWAH - Nadya, Nadya; Rofiki, Moh.; Fajri, Zaenol; Widat, Faizatul; Diana, Eka (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to find out human resource management in improving teachers competence through the training of Qira'ati method in Al-Qur’an Kindergarten of An-Nadwah. The research method is qualitative descriptive method with case study approach. Data collection techniques were carried out by interviews, observation, and documentation. The informants were the principal and 3 teachers selected by purposive sampling technique. Data analysis was carried out using the concept of Milles and Huberman, namely data presentation, data reduction, and conclusions. The result of the study shows that teachers education and training is one of the most effective activities to increasing teachers competence. With the achievement of teachers competence, the quality of teachers in Al-Qur’an Kindergarten of An-Nadwah will increase.